Implementasi Kompetensi Guru PAI dalam Membentuk Karakter Siswa di SMA Wahid Hasyim II Taman Sidoarjo - Iqbal, Muhammad; Masfufah, Masfufah; Majid, Amir Bandar Abdul (YASIN, 2025)
Education aims to enhance the quality of individual lives and provide an understanding of the meaning of life. Studying the reasons and strategies for living a good life makes education a means for individuals to fulfill their responsibilities as stewards on earth. Character education encompasses the application of character values that include aspects of knowledge, will, awareness, and action. The presence of teachers, particularly Islamic Religious Education (PAI) teachers, significantly influences the success of character formation in students at school. This research aims to determine the implementation of competencies of PAI teachers in shaping student character and the supporting and inhibiting factors in this process. The type of research conducted is qualitative descriptive, with the research subjects consisting of three students, one Guidance and Counseling (BK) teacher, and two PAI teachers at SMA Wahid Hasyim II Taman Sidoarjo. The data collection techniques used include observation, interviews, and documentation, with instruments in the form of observation sheets and interview sheets. In data analysis, the researcher performed data reduction, data presentation, and conclusion drawing. The results of the analysis indicate that PAI teachers at SMA Wahid Hasyim II Taman Sidoarjo have implemented four competencies, namely pedagogical competence, personality competence, social competence, and professional competence. In addition, there are two factors that influence the formation of students' religious character and discipline, namely internal factors (will, customs/habits, and personality of the students) and external factors (education and environment). This research is expected to serve as a reference for future researchers interested in analyzing the role of teachers in the formation of student character.